Obstetric nurse: midwives and nurses inheritance (Revista Latino-Americana de Enfermagem, 1998)
There are differences in the generation of nursing and midwifery professions that are in the history of professional practice and teaching. The Social Representation Theory is useful as a framework to study the way obstetrics was inserted in nursing, to understand why teaching was united and to make explicit the reflexion on these transformations to the professional practice. A preliminar analysis points out that the consolidation of the social representation of the obstetric nurse has been done with difficulties, as in nursing context, the reified and the consensual universes of thinking related to this question rarely are convergent.